Foraging behavior of understorey birds in Unimas campus - Ku Nor Azlina, Binti Ku Nasradhi (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The studies on foraging ecology of birds are important to describe their community structure and the availability of food resources in their habitat. The behavioral study of 19 species of birds was conducted in Universiti Malaysia Sarawak (UNIMAS) campus at Kota Samarahan, Sarawak. The objectives of this study are to: (1) describe the foraging behavior of selected bird species, (2) understand the guild structure of birds in the habitat and (3) analyze the niche overlap and explore the network interaction between bird species. The foraging activities of birds were observed for six months along a predetermined line transect. A total of 1189 observations were recorded and analyzed based on the basic foraging component such as foraging height, foraging technique, foraging substrate, and types of food. Foraging activity depends on the availability of food in their habitat, plant species, foraging height, and prey-attack behavior. The niche overlap indicated the competition among the species in the ecological community. Network analysis of bipartite was used to calculate the niche overlap by using Hom index and Multi-variate Statistical Package (MVSP) was used to determine the interrelations among the species. The results showed the highest value (0.61) in the use of foraging technique but less in types of food preferences and foraging substrate (0.42). This study reveals that the birds exploit the habitat with different strategies and niche partitioning allowed the birds to coexist in a habitat which potentially reduce the competition.